2011
DOI: 10.1002/anie.201102318
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed β‐Selective Direct Arylation of Porphyrins

Abstract: Porphyrins are an important class of aromatic compounds that exhibit interesting optical and electrochemical properties and have attracted much attention as key components of functional materials and supramolecular architectures.[1] Creation of new porphyrins that feature intriguing properties is hence essential in developing the chemistry and applications of functional p-rich molecules. Peripheral functionalization of porphyrins can effectively modify the electronic and steric nature of the parent porphyrins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 59 publications
2
25
0
1
Order By: Relevance
“…Therefore, an additional impact of the β‐tolyl groups aside from macrocycle distortion might arise from their electronic effects. In line with the calculations performed for 2 , Kawamata et al . found much lower dihedral angles for the β‐positions (48–54°) than for the meso ‐positions (86–89°) in the crystal structure of the structurally related nickel porphyrin [2,8,12,18‐tetrakis(3,5‐dimethylphenyl)‐5,15‐bis(3,5‐di‐ tert ‐butylphenyl)porphyrinato]nickel(II).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Therefore, an additional impact of the β‐tolyl groups aside from macrocycle distortion might arise from their electronic effects. In line with the calculations performed for 2 , Kawamata et al . found much lower dihedral angles for the β‐positions (48–54°) than for the meso ‐positions (86–89°) in the crystal structure of the structurally related nickel porphyrin [2,8,12,18‐tetrakis(3,5‐dimethylphenyl)‐5,15‐bis(3,5‐di‐ tert ‐butylphenyl)porphyrinato]nickel(II).…”
Section: Resultssupporting
confidence: 59%
“…Compared with 1 , the first reduction potential of 2 is shifted to a more positive potential of −1.72 V versus Fc/Fc + , whereas 3 has the most negative reduction potential of −1.87 V versus Fc/Fc + . Compound 2 is substantially easier to reduce than 1 , which can be explained by the strong electronic effect of the β‐tolyl substituent, as reported in the literature . The electronic effect of these substituents proves that they are at least to some extent conjugated with the π system of the macrocycle.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Recently, we reported that direct arylation reactions of nickel porphyrins 2 aNi provide β,β′‐diarylporphyrins 3 Ni . Such arylation reactions are not applicable to zinc or free‐base porphyrins 5ac. The denickelation reaction of β,β′‐diphenylated and β,β′‐dinaphthylated porphyrins ( 3 aNi , 3 bNi , and 3 cNi ) resulted in yields comparable to conventional acid‐induced denickelations (Table 3).…”
Section: Methodsmentioning
confidence: 99%